PENERAPAN OMNIBUS LAW DALAM UPAYA REFORMASI REGULASI - Putra, Antoni (Direktorat Jenderal Peraturan Perundang-undang, Kementerian Hukum dan Hak Asasi Manusia, 2020)
Omnibus law is a law that focuses on simplifying the number of regulations because of its revision and repeal of many laws at once. The use of the concept of the omnibus law has not been accommodated in Law Number 12 of 2011, but the use of this concept is not prohibited. This concept is only appropriate to overcome the problem of too many regulations, but the problem of regulation is not only that, there are still disharmonious problems, overlapping, inappropriate material, and sectoral egos from forming institutions. Then, the application of the omnibus law must comply with the principles of transparency, participation, and accountability.